2016
DOI: 10.1128/jvi.01482-16
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-1-Neutralizing IgA Detected in Genital Secretions of Highly HIV-1-Exposed Seronegative Women on Oral Preexposure Prophylaxis

Abstract: Although nonhuman primate studies have shown that simian immunodeficiency virus/simian-human immunodeficiency virus (SIV/SHIV) exposure during preexposure prophylaxis (PrEP) with oral tenofovir can induce SIV immunity without productive infection, this has not been documented in humans. We evaluated cervicovaginal IgA in Partners PrEP Study participants using a subtype C primary isolate and found that women on PrEP had IgA with higher average human immunodeficiency virus type 1 (HIV-1)-neutralizing magnitude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…We measured the effect of oral tenofovir disoproxil fumarate (TDF) and emtricitabine (FTC), or oral TDF alone, on the gastrointestinal tract, the female reproductive tract, and blood from three clinical trials of oral PrEP in HIV-uninfected individuals: the Microbicide Trials Network trial 017 9 (MTN-017); ACTU-3500 (first reported here, see Methods); and the Genital Mucosal Substudy (GMS) 10 of the Partners PrEP Study 8 . We analyzed gene expression by microarray, RNA sequencing (RNAseq) and digital droplet PCR (ddPCR); and protein expression by mass spectrometry and microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the effect of oral tenofovir disoproxil fumarate (TDF) and emtricitabine (FTC), or oral TDF alone, on the gastrointestinal tract, the female reproductive tract, and blood from three clinical trials of oral PrEP in HIV-uninfected individuals: the Microbicide Trials Network trial 017 9 (MTN-017); ACTU-3500 (first reported here, see Methods); and the Genital Mucosal Substudy (GMS) 10 of the Partners PrEP Study 8 . We analyzed gene expression by microarray, RNA sequencing (RNAseq) and digital droplet PCR (ddPCR); and protein expression by mass spectrometry and microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were used from four studies, which are described in Table 1. Two sets of samples were used from the Genital Mucosal Substudy (GMS) 10 Table 1). ACTU-3500 was reviewed through the University of Washington Institutional Review Board, number 49167.…”
Section: Studiesmentioning
confidence: 99%
“…Levels of cervical mucosal IgA have been correlated with the frequency of repeated exposure in the absence of any correlation with resistance. 97 Furthermore, the recurrent presence of neutralizing anti-HIV IgA in these cohort studies 87,88,97,98 could possibly be linked to prevention of persistent systemic HIV infection. The reduced risk of infection in these individuals is, however, most likely dependent on multiple interactive factors, and understanding the mechanisms of protection among these populations will likely be key to designing effective vaccine strategies.…”
Section: Neutralization and Prevention Of Hiv Acquisitionmentioning
confidence: 89%
“…A protective role for mucosal IgA is often inferred from studies of individuals referred to as highly exposed to HIV, but IgG seronegative (HESN) individuals, despite repeated sexual exposure to seropositive partners. Many of these studies report detection of anti-HIV IgAs in serum, 86 genitourinary fluids, [86][87][88] and saliva 89 of these individuals who are often from studies examining sex worker cohorts. Some of these studies have correlated resistance with HIV with high levels of IgA against the envelope protein in vaginal secretions and saliva of these HESN individuals.…”
Section: Neutralization and Prevention Of Hiv Acquisitionmentioning
confidence: 99%
“…For women whose cervical/vaginal secretions had neutralizing IgA, the OR for HIV-1 acquisition was 0.31. A later study involving women enrolled in a Pre-Exposure Prophylaxis (PrEP study) also found anti-HIV-1 neutralizing IgA in the cervical/vaginal secretions [56]: the patient population also involved HEPS individuals. Together, these intriguing data from African men and women give a strong indication that mucosal IgA responses, perhaps IgA1 responses, are linked to lowering the risk of HIV-1 acquisition through sexual exposures.…”
Section: Highly Exposed Persistently Seronegative (Heps) Individuals:mentioning
confidence: 92%